PENGARUH JARAK DAN PANAS SINAR LASER TERHADAP HASIL ENGRAVING PADA MATERIAL KAYU MENGGUNAKAN MESIN CNC LASER DIODE - Didik Sugiyanto; Aep Saeful Uyun; Dzul Mujahid Jihad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Testing the effect of distance and laser beam heat on engraving results using two specimens as test materials, namely teak wood and durian wood. The testing process is to make circles and rectangles with a diameter of 20 mm which are inputted into the program followed by the engraving process. The results of the engraving are measured how many differences occur so that the results that are closest to the level of precision are obtained with variations in distance and heat in the laser beam. From the results of the distance test, it was found that durian wood has a more precise engraving accuracy with a size of 0.15-0.35mm, while for teak wood with a size of 0.2-0.4mm. With reference to the general tolerance of medium in sizes >6-30mm is 0.2mm, the best result for the use of spacing is 70mm. From the results of laser heat testing, it was found that durian wood has a more precise engraving accuracy with a size of 0.05 - 0.7mm, while for teak wood with a size of 0.1-0.8mm. With reference to the general tolerance of medium in size >6-30mm is 0.2mm and size >30-120mm is 0.3mm, the best temperature result for use is 400C with a tolerance size of 0.05mm.